2012
DOI: 10.1364/ol.37.002970
|View full text |Cite
|
Sign up to set email alerts
|

Light sources generating far fields with tunable flat profiles

Abstract: Planar, scalar, optical Schell-model, and quasi-homogeneous sources with correlations that are Fourier transforms of multi-Gaussian functions are introduced. It is demonstrated that far fields produced by these families of sources carry interesting characteristics, being flatlike with adjustable steepness of the edge. Beam conditions for such sources are also derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(108 citation statements)
references
References 8 publications
1
101
0
Order By: Relevance
“…Partially coherent fields can cause several different kinds of modifications to the spatial intensity distribution, such as self-focusing and far-field flat topping, among many others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, they are not the only extraordinary phenomena caused by partial coherence; some correlation functions can decrease scintillation in atmospheric turbulence [17], while others increase the resolving power of imaging systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Partially coherent fields can cause several different kinds of modifications to the spatial intensity distribution, such as self-focusing and far-field flat topping, among many others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However, they are not the only extraordinary phenomena caused by partial coherence; some correlation functions can decrease scintillation in atmospheric turbulence [17], while others increase the resolving power of imaging systems [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The far field generated by RGSM beam propagating in free space may have flat square/rectangular intensity distribution, which is different from the flat circular intensity distribution produced by the multiGaussian Schell model beams or the electromagnetic sinc Schellmodel beams [2][3][4][5]. The pattern of the RGSM beam throughout far field keeps invariant.…”
Section: Introductionmentioning
confidence: 92%
“…Various partially coherent beams with prescribed correlation functions have been investigated in both theory and experiment since Gori and collaborators derived the sufficient condition for constructing the genuine correlation functions [2,3] . Recent studies have shown that specially correlated partially coherent beams display many unique but interesting properties, e.g., self-splitting effect appears in a Hermite-Gaussian correlated Schellmodel beam on propagation [9][10][11] , partially coherent beams with multi-Gaussian, Bessel-Gaussian and cosine-Gaussian correlated Schell-model functions exhibit prescribed farfield intensity distributions [12][13][14][15] , Laguerre-Gaussian correlated Schell-model beam produces an optical cage near the focal plane [16,17] . Due to those extraordinary properties, specially correlated partially coherent beams are useful in some applications, such as optical imaging, particle trapping, atom guiding and free-space optical communications.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-Gaussian correlated Schell-model (MGCSM) beam introduced in Ref. [12] displays far-field flat-topped beam profile although it has a Gaussian beam profile in the source plane [12,23] . Both theoretical and experimental results have demonstrated that an MGCSM beam exhibits lower scintillation than a GSM beam in turbulence [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%